2006
DOI: 10.1186/1471-2407-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Over-representation of specific regions of chromosome 22 in cells from human glioma correlate with resistance to 1,3-bis(2-chloroethyl)-1-nitrosourea

Abstract: BackgroundGlioblastoma multiforme is the most malignant form of brain tumor. Despite treatment including surgical resection, adjuvant chemotherapy, and radiation, these tumors typically recur. The recurrent tumor is often resistant to further therapy with the same agent, suggesting that the surviving cells that repopulate the tumor mass have an intrinsic genetic advantage. We previously demonstrated that cells selected for resistance to 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU) are near-diploid, with over-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In preliminary studies reported for BCNU, the authors identified four miRNAs (let-7b, mir-125b-2, mir133a-1, and mir-183) that were differentially expressed in both primary vs. recurrent GBMs and BCNU sensitive vs. resistant cells. Of these, let-7b is mapped to chromosome 22q12, a region previously correlated by the same group to be correlated with GBM resistance to BCNU (Hank et al, 2006).…”
Section: Figmentioning
confidence: 99%
“…In preliminary studies reported for BCNU, the authors identified four miRNAs (let-7b, mir-125b-2, mir133a-1, and mir-183) that were differentially expressed in both primary vs. recurrent GBMs and BCNU sensitive vs. resistant cells. Of these, let-7b is mapped to chromosome 22q12, a region previously correlated by the same group to be correlated with GBM resistance to BCNU (Hank et al, 2006).…”
Section: Figmentioning
confidence: 99%
“…This can be verified in individual cases by methylation-specific PCR on resected tumor tissue which allows identification of patients more likely to respond favourably to the treatment (Paus et al, 2007). Glioma cells that are resistant to BCNU typically have overrepresentation of chromosome 22q12.3-13.32, implying that this chromosome region contains genes important for BCNU resistance (Hank et al, 2006). Resistance of gliomas to alkylators and recurrence of disease after therapy with alkylators are also proportional to the activity in these tumors of apurinic/apyrimidinic endonuclease, a DNA repair enzyme that cleaves DNA at the abasic sites formed by alkylating chemotherapy and radiation (Bobola et al, 2004).…”
Section: Gliomas and Glioblastomasmentioning
confidence: 99%